Developing a Badge System for a Community ESL Class Based on the Canadian Language Benchmarks - McCollum, Robb Mark; Reed, Elena Tornar (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2020)
Teaching multilingual, multilevel language classes presents many challenges including helping students learn level-appropriate language. This learner-centred approach is complicated in a multilevel classroom where the teacher cannot always focus on each student’s needs. As a result, learner motivation and attendance are frequent problems. This article details the adaptation of the Canadian Language Benchmarks (CLB) into a badge system to help learners in a community English as a Second Language (ESL) program set and track personalized language learning goals. The authors explain the purposes of badges, including motivation and assessment, and describe how to create a CLB-based badge system for curriculum and assessment purposes. The authors also share feedback from students and instructors in the community ESL program about the badge-based curriculum.